Impact of System Digitalization Administration through Training Microsoft Office and Google Workspace (SMK Sjakhyakirti) - Cahyo Pambudi Darmo; Andika; Lemi Iryani; Putri Maharani (CogniSpectra Publishing, 2025)
BackgroundDevelopment technology information and communication has push transformation in various sectors, including administration education. However, many school medium vocational schools (SMK) which are still use method administration conventional, so that cause delay data processing ,irregularity storage, and low efficiency work. Challenge This become the more relevant in the digital era, when ability power education For utilise technology become need urge. Contribution: Activity devotion This give contribution real in the form of training use of Microsoft Office and Google Workspace for power educators and staff administration at Sjakhyakirti Vocational School. Training This expected be a role model for other schools in apply digitalization administration based technology. Method: The method used is participatory and applicable with approach qualitative activities​ started with identification needs, preparation materials, training direct, practice independent, simulation task administrative, as well as evaluation through practice and questionnaire bait come back. Results: Results of activities show that 90% of participants capable using Microsoft Word, Excel, PowerPoint, Google Docs, Sheets, and Slides to finish task administrative in a way independent. In addition , 85% of participants succeed implement cloud storage via Google Drive and online collaboration. Conclusion: Training This succeed increase digital competence of participants, strengthening the digitalization process administration school, and build culture more work​ efficient and collaborative in the SMK Sjakhyakirti.